2008
DOI: 10.1007/s00213-008-1351-0
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase A2 activation as a therapeutic approach for cognitive enhancement in early-stage Alzheimer disease

Abstract: The use of positive modulators of PLA2 (especially of cPLA2 and iPLA2) or supplementation with dietary lipid compounds (e.g., arachidonic acid) in combination with cognitive training could be a valuable therapeutic strategy for cognitive enhancement in early-stage AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 176 publications
1
30
0
Order By: Relevance
“…Therefore, it is plausible to suggest that higher Pla2 activity, or specifically the iPla2 subgroup, could play a key role in the genesis of a better memory retrieval, which in our study was observed in animals treated with lithium. Furthermore, our group recently demonstrated that rats fed with a high conjugated linoleic acid diet (which modulates PLA2 activity) showed increased memory and higher hippocampal PLA2 levels [83], in line with other groups that showed the positive impact of polyunsaturated fatty acids and memory in elderly subjects [84,85].…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, it is plausible to suggest that higher Pla2 activity, or specifically the iPla2 subgroup, could play a key role in the genesis of a better memory retrieval, which in our study was observed in animals treated with lithium. Furthermore, our group recently demonstrated that rats fed with a high conjugated linoleic acid diet (which modulates PLA2 activity) showed increased memory and higher hippocampal PLA2 levels [83], in line with other groups that showed the positive impact of polyunsaturated fatty acids and memory in elderly subjects [84,85].…”
Section: Discussionsupporting
confidence: 83%
“…Consistently, the predominant PLA 2 activity in rodent hippocampal slices was reported to be manifested by iPLA 2 and to be essential for synaptic plasticity , as refl ected in iPLA 2 inhibition studies ( 311 ). This was later confi rmed in whole animal studies ( 141 ), leading to the suggestion that reductions in cPLA 2 and iPLA 2 activities can have adverse effects on memory in patients with Alzheimer's ( 312 ). These studies, however, did not distinguish which iPLA 2 ( ␤ or ␥ ) isoform activity was critical for the dementia associated with targeted genetic knockdowns ( 373 ) …”
Section: Ipla 2 ␤ and Diseasesmentioning
confidence: 99%
“…Since cholinergic neurons influence the neurocognitive attentional function of rodents and humans, cholinergic drugs (acetylcholine esterase inhibitors) or NGF gene injection into BCNs have improved attention deficits and cerebral metabolism in early-stage AD [5,7,46,47,48,49]. Of the six components, the go/no-go is known as ‘inhibition control’, a conduct that inhibits inappropriate responses and regulates impulsions [36].…”
Section: Discussionmentioning
confidence: 99%
“…Among the main nonmemory neurocognitive impairments during the initial stage of AD or during amnestic mild cognitive impairment (A-MCI), executive dysfunction and attentional impairment have been shown to occur before deficits in language and visuospatial function, with the progression of cholinergic neuron degeneration beginning during the early phase [1,2,3,4,5,6,7]. From a longitudinal aspect, MCI patients with memory and executive function/psychomotor speed deficits have a higher risk of converting to AD than patients with only memory deficits [8].…”
Section: Introductionmentioning
confidence: 99%